Chemokine‐Capturing Wound Contact Layer Rescues Dermal Healing (Adv. Sci. 18/2021). Issue 18 (22nd September 2021) - Schirmer, Lucas; Atallah, Passant; Freudenberg, Uwe; Werner, Carsten
Abstract : Wound Healing Excessive inflammation often impedes the healing of chronic wounds. In article number 2100293, Lucas Schirmer, Carsten Werner, and co‐workers report a glycosaminoglycan hydrogelcoated wound contact layer capable of selectively sequestering pro‐inflammatory chemokines. A large animal model of human wound healing disorders confirms that the approach dampens inflammation without affecting pro‐regenerative growth factors, thus expanding the scope of a new anti‐inflammatory therapy toward clinical use.